CRISPR Cas9-mediated ablation of pyruvate carboxylase gene in colon cancer cell line HT-29 inhibits growth and migration, induces apoptosis and increases sensitivity to 5-fluorouracil and glutaminase inhibitor - Ngamkham, Jarunya; Siritutsoontorn, Siraprapa; Saisomboon, Saowaluk; Vaeteewoottacharn, Kulthida; Jitrapakdee, Sarawut (Frontiers in Oncology, 2022)
Pyruvate carboxylase (PC) is an important anaplerotic enzyme which replenishes the tricarboxylic acid cycle intermediates, enabling cells to synthesize biomolecules during high bioenergetic and anabolic demands. We have recently showed that overexpression of PC protein was associated with staging, metastasis and poor survival of colorectal cancer patients. Herein, we generated the PC knockout (PC KO) colon cancer cell lines, HT-29 by CRISPR-Cas9 technique as a model to understand role of this enzyme in colorectal cancer. The PC KO HT-29 cell lines had no detectable PC protein and did not show abnormal cellular or nuclear structures. PC KO HT-29 cells showed 50-60% reduction of their growth rate, accompanied by 60-70% reduction of migration. The growth deficient phenotype of PC KO HT-29 cells was found to be associated with apoptotic induction with no apparent disruption of cell cycle following 5 days of growth. Down-regulation of key lipogenic enzymes including acetyl-CoA carboxylase-1 and fatty acid synthase was also associated with growth inhibition, suggesting that the de novo lipogenesis is impaired. Furthermore, PC KO HT-29 cells were 50% more sensitive to 5-fluorouracil and 60% more sensitive to glutaminase inhibitor, CB-839, following 48 h exposure to either of the drugs. The increased cytotoxicity of CB-839 to PC KO HT-29 cells was associated with increased poly (ADP-ribose) polymerase cleavage while this was not observed with PC KO cells exposed to 5-fluorouracil, suggesting that PC KO HT-29 cells were prone to CB-839-induced apoptosis. Taken together, these findings suggest that ablation of PC expression in HT-29 cells disrupts metabolic homeostasis of cells, inhibits proliferation and migration, accompanied by apoptotic induction. This study highlights the crucial role of PC in supporting survival of HT-29 cells during exposure to the chemotherapeutic drugs.